2016
DOI: 10.1111/asj.12648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2‐hydroxy‐4‐(methylthio) butanoic acid isopropyl ester on growth and blood components in growing Holstein steers

Abstract: Twenty-four Chinese Holstein growing steers were randomly divided into three groups and fed a diet containing 0 (the control group), 15 (treatment I group, or TG1) or 25 (treatment II group, or TG2) g/day 2-hydroxy-4-(methylthio) butanoic acid isopropyl ester (HMBi). Compared with the control group, the final body weights, total gains and average daily gains in the treatment groups increased (P < 0.01). The concentration of total protein (TP) for TG1 increased (P < 0.01). The levels of albumin in TG1 were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Similarly, decreased sensitivity of hepatic GH was caused by a decrease of GH receptor mRNA in the liver of rats (Bornfeldt et al 1989;Straus & Takemoto 1990). Similar experiments to the current experiment (Elsasser et al 1989;Tripp et al 1998;Han et al 2017) showed that in general, administration of bST increased the concentration of IGF-1 in the circulation but this was sensitive to the nutritional status of the animal or the diet.…”
Section: Plasma Hormones Metabolites and Bone Metabolism Markerssupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, decreased sensitivity of hepatic GH was caused by a decrease of GH receptor mRNA in the liver of rats (Bornfeldt et al 1989;Straus & Takemoto 1990). Similar experiments to the current experiment (Elsasser et al 1989;Tripp et al 1998;Han et al 2017) showed that in general, administration of bST increased the concentration of IGF-1 in the circulation but this was sensitive to the nutritional status of the animal or the diet.…”
Section: Plasma Hormones Metabolites and Bone Metabolism Markerssupporting
confidence: 80%
“…Similarly, the decreased sensitivity of hepatic GH was caused by the decrease of GH receptor mRNA that was observed in the rats' liver (Bornfeldt et al 1989;Straus & Takemoto 1990). Similar experiments suggest that the increase in IGF-1 in response to bST administration is sensitive to nutritional intake (Elsasser et al 1989;Tripp et al 1998;Han et al 2017). Therefore, nutritional metabolisable energy restriction here prevented the effectiveness of bST in promoting growth with or without a high CP supply.…”
Section: Plasma Hormones Metabolites and Bone Metabolism Markersmentioning
confidence: 54%
“…As methyl donors, rumen protected choline has been reported to improve growth performance of cattle ( Bindel et al, 2000 ). Han et al (2017) also observed the supplementation of methionine improved growing Holstein steers’ performance. Hussein and Berger (1995) also showed that feeding rumen-protected methionine and rumen-protected Lysine to Holstein steers improved average daily gain.…”
Section: Discussionmentioning
confidence: 76%
“…The results were in agreement with Čermáková et al [ 31 ] who reported that supplementing HMBi at 0.16% DM did not affect the plasma concentrations of total protein and urea in dairy cows fed a diet based on alfalfa, corn silages, and ensiled corn cobs. However, Han et al [ 14 ] reported that supplementing HMBi at 25 g d −1 increased the serum concentrations of total protein and albumin and decreased the serum concentration of urea in steers fed a diet based on corn silage and corn. The discrepancy in the results could be resulted from the extent of dietary Met supply (including Met from HMBi) to meet the requirements of animals among different experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementing HMBi to the diets of dairy cows at 0.13% DM reduced the N excretion and improved the N utilization rate [ 13 ]. Supplementing HMBi to the diet of growing Holstein steers at 15 or 25 g d −1 improved the daily liveweight gain and the plasma total protein concentration [ 14 ]. Other studies, however, showed that supplementing HMBi to the diets of dairy cows at 0.26% DM had no effect on the milk protein yield [ 15 ], and supplementing HMBi at 0.17% DM [ 16 ] and 0.20% DM [ 17 ] did not affect the N excretions.…”
Section: Introductionmentioning
confidence: 99%